Analysis of the clinical characteristics of bone metastases after pheochromocytoma/paraganglioma surgery - Li, Longmin; Gao, Hongbo; Shao, Yujun; Zhu, Xiayang (Frontiers in Endocrinology, 2025)
BackgroundPheochromocytomas and paragangliomas (PPGLs) frequently metastasize to bone. We aimed to investigate the clinical characteristics of PPGL patients with postoperative bone metastases (BMs) in hopes of providing valuable insights into future clinical practices for patients with PPGLs.MethodsIn this retrospective study, 107 patients were enrolled. The clinical, pathological and laboratory examination results of the patients were analyzed. We statistically investigated the clinical characteristics of BMs in PPGLs. Logistic regression analysis was used to determine the factors influencing BMs, and a Cox proportional hazards regression model was used to evaluate the prognostic factors of bone metastasis-free survival (BMFS) in patients with PPGLs.ResultsEighty-one of the 107 patients (75.7%) developed BMs, and BMs occurred at a median of 60 months after complete resection of the primary mass (range, 3–308 months). Most bone lesions were multiple (54 patients [66.7%]), and the spine was the most frequent site of bone involvement (229 lesions [63.3%]). Skeletal complications occurred in 31 patients (38.3%), of whom bone pain was the most common symptom (90.3%). Fifty-eight patients were grouped according to whether they had bone metastases or not. Logistic regression analysis revealed that SDHB mutation (OR=5.334, 95% CI: 1.072–26.534, P=0.041) was an independent risk factor for bone metastases in PPGLs. The median duration of bone metastasis-free survival in the 58 patients with PPGLs was 101 months (range, 3–308 months). Multivariate Cox regression analysis revealed that SDHB mutation (HR=3.376, 95% CI: 1.470–7.754, P=0.004) was an independent poor prognostic factor for BMFS in patients with PPGLs.ConclusionsPPGLs exhibit a pronounced tropism for bone, metastasizing to the skeletal system with higher frequency than to organs like the liver or lungs. These bone metastases are frequently associated with skeletal complications. SDHB mutation is a risk factor for bone metastases in PPGLs. It is crucial to emphasize genetic detection and postoperative follow-up examinations in patients with PPGLs.